The Reliability and Validity of the Vietnamese translation of Same-Sex Marriage Scale (Revista de Investigaciones Universidad del Quindío, 2023)
Vietnam, in many ways, remains a Confucian nation. The Confucian heritage touches many aspects of people’s lives. In this context, homosexuals  do not face severe punishments, but face social stigma or public misunderstanding.  Same-Sex Marriage is also not accepted because of limited legal support. Therefore, there is a need to study attitudes towards same-sex marriage in Vietnam. The purpose of this article was to validate a Vietnamses version of the Attitudes Toward Same-Sex Marriage Scale (ATSM) designed by Pearl & Galupo (2007) in a Vietnamese population. The sample in this study was 570 students from six universities in Ho Chi Minh City, Vietnam. The data collection method used was face-to-face questionnaire. Students completed the Attitudes Toward Same-Sex Marriage Scale and other variables in the questionnaire. The respondent’s characteristics also explored through the survey include: gender, what year students are from, religion of the students, what region students are from and their ethinicity. The study found the Vietnamese translation of the ATSM scale both reliable and valid and suitable for research use.
Keywords: Same-sex marriage; Homosexuality; Sexual orientation; Attitudes; Viennam